Linguistic Features of the Earliest Copy of the Didactic Gospel by Constantine the Presbyteros: From the East Slavic Manuscript to the South Slavic Archetype - Roman N. Krivko (Slovene, 2016)
The article is dedicated to the linguistic features of the Didactic Gospel by Constantine the Presbyteros, who is also known as Constantine of Preslav or Constantine of Bregalnica. The earliest witness of the original text, which Constantine wrote down at the end of the 9th century in the First Bulgarian Kingdom, is the Old East Slavonic manuscript dating to the end of the 11th–beginning of the 12th centuries (this manuscript is sometimes dated to a later period). The manuscript is remarkable for its graphic and orthographic features characteristic only for the earliest Church Slavonic sources of East Slavonic provenance; these sources are dated to the 11th century or to the beginning of the 12th century. At the same time, the manuscript attests phonetic innovations caused by the initial stage of the loss of the jer-vowels, such as “new jat’” and the change of e into o. On the basis of the earliest manifestations of the change of e into o in the written sources, the author argues that this phonetic change took place in the southern part of the East Slavonic area and first of all in the prefinal syllable before the final jer in the absolute weak position. Phonetic and orthographic peculiarities of the East Slavonic witness of the Didactic Gospel testify to the southwest Balkan provenance of its South Slavonic protograph, which must have been a Cyrillic one. (On the basis of lexical data, the southwest Balkan origin of Constantine’s archetype was argued by the author elsewhere.) From the point of view of verbal morphology, the earliest witness of the Didactic Gospel seems to be one of the most archaic East Slavonic manuscripts, which is particularly testified by a number of forms of the root aorist. Special attention is devoted to the construction called “relativer Attributivkonnex” (Ch. Koch). It was discovered by scholars in a number of South Slavonic sources or in East Slavonic manuscripts which go back to the South Slavonic tradition, and is to be observed in the Didactic Gospel, too.